Genetic crosstalk of autism spectrum disorders and epilepsy: an insight into the presynapse - Sharma, Mahima; Pamidi, Sai Charan; Divi, Pavan Kumar; Mohapatra, Saswati; George, Brijit; Sneha, Karen P.; Kreutzmann, Judith C.; Annamneedi, Anil (Frontiers in Neurology, 2025)
The neurodevelopmental disorder autism spectrum disorder (ASD) affects 0.5%–1% of the global population and is marked by ongoing difficulties in social communication and cognitive function. Interestingly, ASD has been reported to share a genetic origin with epilepsy, a condition marked by recurrent, unprovoked seizures. Both ASD and epilepsy are caused by multifactorial and multigenetic origin. Whereas the number of genes linked to ASD etiology are growing, the genetic basis of epilepsy is more diverging leading to distinct epileptic syndromes. Despite decades of discussion, a comprehensive understanding of the genetic interplay between these disorders remains elusive. Our article focuses on investigating the shared genetic basis of abnormalities in synaptic proteins, highlighting the presynaptic compartment, which is less explored compared to the postsynaptic elements. We identify those biological processes linked to the presynaptic compartment, such as presynaptic assembly, ATP metabolism, various aspects of the synaptic vesicle cycle, are commonly affected across conditions, as evidenced by the shared genetics. Hence, this study offers initial insights into presynaptic signaling, and further research could aid in developing improved therapeutic strategies by targeting these presynaptic processes.